Wavelength tuning of a passively Q-switched Er-doped fiber laser based on a Tm–Ho codoped fiber saturable absorber. (21st September 2018) - Tao, Mengmeng; Yu, Ting; Chen, Hongwei; Shen, Yanlong; Ye, Xisheng; Zhao, Jun
Abstract: With a piece of Tm–Ho codoped fiber as the saturable absorber, stable passive Q-switching of an Er-doped fiber laser can be attained in a wide wavelength range. A theoretical model concerning this passively Q-switched laser system with wavelength tuning is established. Output characteristics of this laser system are discussed and compared both experimentally and numerically. Analysis shows that, for saturable absorber-based passive Q-switching, a relatively higher coupling ratio and a longer wavelength not only help to expand the pump range and the repetition rate range of the laser system, but also indicate higher output energy and Q-switching efficiency.